Financiamento público para a área da saúde em cidades gêmeas do estado do Paraná de 2000 à 2016 - Santos, Cleide Teresinha dos (2018)
The Unified Health System, created in 1988, was one of the main achievements of Brazilian society in the twentieth century, as far as social rights are concerned. It is the largest public policy in force, despite the many unresolved problems in its three decades of existence, for instance problems of access, management capacity, training of human resources, regional organization, training of networks and lack of public funding. In border municipalities and especially in twin cities, the problems are gaining new ground in the face of free border traffic and the disparity between health systems in different countries. At the borders, there are specifics that deserve to be analyzed since different political, monetary, security and social protection systems coexist there: the intensification of flows resulting from this integration creates new challenges for health systems, requiring specific policies aimed at ensuring the right to health in those regions. The present study aims to analyze the trajectory of resources and public expenditures with actions and health services in four twin cities in the state of Paraná from 2000 to 2016 and to identify how the border problem appears in the SUS planning and management instruments. This is a descriptive, cross-sectional, quantitative and exploratory research, developed from secondary data. Data collection was performed in the Information System on Public Budgets in Health, comprising the total expenditure spent on health actions and services for large items of Current and Capital Expenditures and in the SUS Management Report Support System, where it sought information on SUS planning and management tools: Municipal Health Plan, Annual Health Program and Annual Management Report. Data were presented in the form of tables and graphs and analyzed using simple descriptive statistics. The results showed a growth of the values applied in actions and health services over time, it was verified that the current expense represents the summary value superior to the capital expense with progressive and continuous value in the study timeline. In terms of local specificity, there was a lack of continuity in specific transfers to border areas and little information in the Planning and Management Instruments of the SUS on the border issue.